HIV disclosure to sexual partner and associated factors among women attending ART clinic at Mekelle hospital, Northern Ethiopia - Alemayehu, Mussie (BioMed Central, 2014)
BACKGROUND: Disclosure of HIV positive status has two sets of contrary effects. It may motivate partner for Voluntary Counseling and Testing; on the other hand, it may cause blame, discrimination, depression and loss of economic support. Consequently, HIV positive status disclosure among women has become one of the major concerns that should be addressed in HIV prevention and control activities. This study aimed at assessing the magnitude and factors related to HIV positive status disclosure to sexual partners among HIV positive women. METHODS: A cross sectional study was conducted in Mekelle hospital from July 10–26, 2013 to collect data from 315 HIV positive women using a systematic random sampling. Descriptive and multiple logistic regression analyses were performed using SPSS 20 for windows to estimate indicators and effect sizes of the predictors on HIV disclosure status to partners. RESULTS: The proportion of HIV disclosure status to their partner was 63.8%. Women who knew the HIV status of their sexual partner and those who got pretest counseling had a positive association with HIV disclosure with AOR of 16.9 (95% CI: 8.11, 35.21) and AOR of 2.8 (95% CI: 1.83, 4.28). Mothers with two years or beyond, since they knew their HIV status had more odds (AOR = 3. 2, 95% CI: 1.7, 6.29) to disclose their HIV status to their partner. Mothers who had seen people with HIV positive who disclose their HIV status to the community (AOR = 2.1, 95% CI: 1.08, 4.01) and those who had a discussion prior to HIV testing (AOR = 4.87, 95% CI: 2.45, 9.71) were more likely to disclose their HIV status than their counterparts. CONCLUSIONS: The rate of HIV disclosure to their partner was low. Knowledge of HIV status of partner, receiving pretest counseling, longer time since the HIV testing, know people who disclose their status to the community and having discussion prior to HIV testing could influence disclosure of HIV status of mothers to their partners.